The Effect of Temperature and Fermentation Time Using Local Microorganism on Robusta Coffee Characteristics - Joko Suryadi; Ardika Rizki Subagja; Arini Nur Amalia; Tri Hariyadi (Department of Chemical Engineering, Politeknik Negeri Bandung, 2025)
Robusta coffee beans are known to have higher caffeine levels compared to other coffee beans. Fermentation is one of the steps to reduce caffeine levels in coffee. This study aims to determine the effect of temperature and fermentation time on robusta coffee characteristics consisting of testing caffeine content, ethanol content, moisture content and pH. The fermentation process of coffee beans is carried out using local microorganism cassava tapai. The local microorganism of cassava tapai was chosen because it can be a source of microbial activity. Fermentation of coffee beans was carried out anaerobically with temperature variations of 30ºC and 37ºC and with fermentation time variations of 0, 6, 12, 18, 24, 30, 36, 42 and 48 hours. The results showed that the longer the fermentation time, the lower the caffeine content. Caffeine levels decreased from 4.88% to 2.53% ± 0 and 3.73% ± 0 at the 30ºC and 37ºC temperature variations at the longest time variation (48 hours). The degree of acidity or pH value decreased from 5.10 to 4.38 ± 0 and 4.27 ± 0,01. Moisture content is relatively fluctuating but all sample variations are in the standard range of 10-12.5%. Whereas ethanol content increased from 2.46% to 4.36% ± 0 and 4.26% ± 0,13. Through the P-value ANOVA Two Factor Without Replication test, it can be concluded that fermentation temperature has a significant effect on caffeine content and pH, while fermentation time has a significant effect on caffeine content, ethanol content and pH.